(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study is identifying the factors influencing their nursing work performance and to provide a preliminary data necessary for managing nursing manpower by examining the nursing work performance, job satisfaction, and self leadership of nurses in medium sized hospitals. Methods/Statistical analysis: This study is a survey was carried out targeting nurses selected by using the convenience sampling method who have been working for more than 6 months in medium sized hospitals. Data analysis was descriptive statistics analysis, t-test, one-way ANOVA, correlation analysis, and multiple regression using SPSS/WIN 22.0 program. Findings: This study showed that the job satisfaction and self leadership were factors significantly influencing the nursing work performance and the explanation power of job satisfaction and self leadership was 40.4%. Improvements/Applications: Therefore, it is suggested that a strategy to improve the job satisfaction and self leadership as a continuous intervention strategy that can maximize the nursing work performance is necessary.